LEADERSHIP STYLES AND ACADEMIC PERFORMANCE OF PUPILS IN SELECTED PUBLIC PRIMARY SCHOOLS: A CASE OF SELECTED SCHOOLS IN JINJA, UGANDA - Ketrah, Amoding Agnes; Musa, Muwaga; Abdu, Wamaungo Juma (FASTABIQ: JURNAL STUDI ISLAM, 2023)
In a bid to address poor academic performance among students in Jinja City primary schools, this study looked into how students' academic performance was affected by school leadership styles within the theoretical framework of the Path-Goal theory of leadership. The goals of the study were to: 1) comprehend how the laissez-faire leadership style affects academic performance; 2) examine the authoritarian leadership style; and 3) ascertain how the democratic leadership style affects students' academic performance. Data collection and analysis were done using a cross-sectional survey design that combined quantitative and qualitative research methods. Using simple random and purposeful sampling techniques, 100 participants were chosen from a target population of 300. Through the use of questionnaires and interview guides, data was gathered. The Statistical Package for Social Sciences (SPSS) was used to analyze the quantitative data, and descriptive analysis was used to find patterns and trends in the qualitative data. The findings revealed that the laissez-faire leadership style significantly affected students' academic performance by 83%. The authoritarian leadership style accounted for 66.7% of the variation in academic performance, while the democratic leadership style contributed 74.1%. The research emphasized the importance of upholding existing school rules, regulations, and goals to enhance students' academic performance. Recommendations include adopting flexible leadership approaches by school heads, emphasizing school rules and regulations, and recognizing the significance of authority in leadership to boost and sustain academic performance. The research also highlighted the value of open communication, guidance, equitable treatment, and equal opportunities for all stakeholders involved in promoting desired academic outcomes in primary schools. The theoretical implication of this study lies in the demonstration that adaption of different leadership styles can be applicable to educational settings to achieve desired goals.Keywords: Leadership Styles; Academic Performance; Path-Goal theory; Educational Outcomes; School Management; Students